Yuan Mei: Recipes from the Garden of Contentment: Yuan Mei’s Manual of Gastronomy - Jaine, Tom (Petits Propos Culinaires, 2018)
Yuan Mei: Recipes from the Garden of Contentment: Yuan Mei’s Manual of Gastronomy, translated and annotated by Sean J.S. Chen: Berkshire, 2019: 468 pp., hardback, 105.00.